Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Hasil Belajar Siswa Pada Materi Bentuk Molekul Kelas XI IPA SMA Negeri 1 Pasangkayu - Raguwan, Raguwan; Gonggo, Siang Tandi; Sabang, Sri Mulyani (Jurnal Akademika Kimia, 2014)
The study of effect of cooperative learning model of snowball throwing type in the molecule shape had been conducted. This study aims to find out the effect of cooperative learning model of snowball throwing on the student’s study outcome in molecule shape material science of SMA Negeri 1 Pasangkayu for 2013 neadenic year. The samples of study are grade XI Science 3 as experimental class (learning by using cooperative learning model of snowball throwing type) with 30 students and grade XI science 1 as a control class (convensional learning) 30 students. Data collection was conducted by using test instrument of study outcome in molecule shape material wich was validated before. The data analysis obtained average score in experimental class = 77.23 and for control class obtained average score 58.7. Based on the hypotesis analysis with t-test of statistic on the party was obtained the value of tcounted= 5.65 and ttable= 1.671 on a = 0.05. H1 was accepted and H0 was rejected, because tcounted was in area of rejection. This shows that the cooperative learning model of snowball throwing type gave positive effect on student study outcome in the molecule shape material in grade XI science of SMA Negeri 1 Pasangkayu.